2006
DOI: 10.1016/j.crvi.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of conserved lentiviral sequences as landmarks of genomic flexibility

Abstract: Considering that recombinations produce quasispecies in lentivirus spreading, we identified and localized highly conserved sequences that may play an important role in viral ontology. Comparison of entire genomes, including 237 human, simian and non-primate mammal lentiviruses and 103 negative control viruses, led to identify 28 Conserved Lentiviral Sequences (CLSs). They were located mainly in the structural genes forming hot spots particularly in the gag and pol genes and to a lesser extent in LTRs and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In contrast, selection for maintaining essential features in viral genomes dictates that naturally arising variation can be more clustered. Examinations of crossovers in infectious virus in culture revealed that localized homology was a key factor (21,22,197,214). Previously reported recombination between significantly different strains may arise essentially by chance, may rely on residual homology or homology-independent recombination triggers, or may be disproportionately common in short regions of high donor/ acceptor template sequence identity (249,265,316).…”
Section: Sequence Similarity and Recombination Rates: Homologous And mentioning
confidence: 99%
“…In contrast, selection for maintaining essential features in viral genomes dictates that naturally arising variation can be more clustered. Examinations of crossovers in infectious virus in culture revealed that localized homology was a key factor (21,22,197,214). Previously reported recombination between significantly different strains may arise essentially by chance, may rely on residual homology or homology-independent recombination triggers, or may be disproportionately common in short regions of high donor/ acceptor template sequence identity (249,265,316).…”
Section: Sequence Similarity and Recombination Rates: Homologous And mentioning
confidence: 99%